Nutrition in Lifestyle Medicine - Rippe, James M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana Press, 2017)
This newest addition to the Nutrition and Health series focuses on nutrition$1 (Bs key role in lifestyle interventions to prevent and manage diseases. The book pays particular attention to nutritional considerations related to obesity, diabetes, and cardiovascular disease. Edited by cardiologist, Dr. James Rippe, a well-known expert in the nascent specialty of Lifestyle Medicine, Nutrition in Lifestyle Medicine will also focus on a variety of specialized areas such as nutrition for athletes and physically active individuals, hydration, and nutrition throughout the life cycle (spanning from children to individuals over the age of 60). In addition, chapters will be included on controversies in nutrition, such as health effects of added sugars and saturated fatty acids in the diet. Finally, specialized chapters will be included in such areas as nutrition for women, nutrition for men, nutrition for latinos, the use of supplements, communication about nutrition, public policy issues, and the interface between nutrition and physical activity. Lifestyle Medicine, supported by the American Journal of Lifestyle Medicine, Dr. Rippe$1 (Bs textbook Lifestyle Medicine (CRC Press, 2013) and American College of Lifestyle Medicine (ACLM), is a new national medicine specialty that stresses the use of lifestyle interventions in the treatment and management of disease. Its practitioners effectively manage medical treatments alongside the lifestyle interventions, for example lowering insulin treatment for patients with diabetes, reducing the dose of anti-hypertension medications for people with hypertension, and prescribing certain medical interventions that aid in smoking cessation.s
Part I. Nutrition in Lifestyle Medicine: General Considerations -- 1. Nutrition in Lifestyle Medicine: Overview -- 2. Nutrition 101: The Concept of Nutritional Status, Standards, and Guides for Nutrient Intakes, Eating Patterns and Nutrition -- 3. Behavior Change and Nutrition -- 4. Effective Strategies to Help Adults Manage How Much They Eat -- 5. Critical Evaluation of Nutrition Research -- 6. Nutritional Genomics: The Wave of the Future for Nutrition and Dietetics -- Part II. Nutrition in Prevention and Treatment of Metabolic Diseases -- 7. The Role of Nutrition and Lifestyle in the Prevention and Treatment of Cardiovascular Disease -- 8. Nutrition Therapy for the Prevention and Treatment of Prediabetes and Diabetes -- 9. Nutrition in Weight Management and Obesity -- 10. Nutrition in Oral Health -- Part III. Nutrition in Childhood -- 11. Childhood Obesity -- 12. Nutritional Interventions to Lower Cholesterol and Risk for Heart Disease in Children -- 13. School Meals: Are they Nutritionally Sound? -- Part IV. Nutrition in Athletes and Physically Active Adults -- 14. Nutritional Considerations for the Active Adolescent -- 15. Effects of an Active Lifestyle on Water Balance -- Part V. Nutrition in Specialized Populations and Conditions -- 16. Nutrition for a Health Pregnancy -- 17. Promoting Nutrition in Men's Health -- 18. Nutritional Considerations for Hispanics -- 19. Optimal Nutrition for the Older Adults -- Part VI. Controversies in Nutrition and Lifestyle Medicine -- 20. Added Sugars and Health: What do we Really Know? -- 21. Saturated Fatty Acids: Friend or Foe? -- Part VII. Nutrition and Public Policy Issues -- 22. Public Policy and Environmental Supports for Healthy Eating -- 23. Food Safety.
Keywords: Medicine; Health promotion; Clinical nutrition; Medicine & Public Health; Clinical nutrition; Health Promotion and Disease Prevention